Farmer Empowerment through Cooperatives in Rural Areas of Tulungagung, East Java: A Model for Strengthening the Local Economy Based on Community Participation - Miya Dewi Suprihandari; Amin Sadiqin (Brilliant International Journal Of Management And Tourism, 2026)
This study aims to analyze the role of agricultural cooperatives in empowering farmers in rural areas of Tulungagung, East Java, focusing on economic and social aspects, and examining the extent to which farmer community participation serves as the foundation for building a sustainable local economic empowerment model. This qualitative research using a case study approach was conducted at the “Makmur Abadi” Farmers Cooperative in Tulungagung Regency. The research findings indicate that cooperatives play a significant role in empowering farmers through: (1) Access to more affordable capital and agricultural inputs, reducing dependence on middlemen (a pattern consistent with the findings of Bijman et al., 2014 regarding the role of farmer organizations); (2) Capacity building through agricultural technical and management training; (3) Strengthening bargaining positions in the market through a collective marketing system; and (4) Building social capital through networking and trust among members. Active member participation in decision-making (Rondot & Collion, 2001) is the main key to maintaining the accountability and sustainability of cooperatives. However, the main challenges lie in limited managerial capacity and market price fluctuations. Agricultural cooperatives in Tulungagung have proven effective as a model for strengthening the local economy based on community participation. Recommendations for similar models to be replicated in other rural areas with adaptations to local contexts emphasize the principle of participation as the key to empowerment (Chambers, 1995).